(untitled) (Baghdad Science Journal, 2024)
An easy, eclectic, precise, and high-performance liquid chromatography (HPLC) analysis was developed and validated for the estimation of S-phenyl mercapturic acid in urine. The chromatographic separation was achieved using a separation column of the ODS-3 Inertsil type with dimensions of (5μ ,150mm x 4.6mm). The column temperature was set at 45° C. A mobile phase composed of acetonitrile: methanol: deionized water acidified with perchloric acid 60% (v/v/v ratio of 4:1:5, pH=3) was used at a flow rate of 1.5 ml/min and a wavelength of 225 nm for UV detection. System Suitability tests (SSTs) are typically performed to assess the suitability and effectiveness of the entire chromatography system. Retention times of S-phenyl mercapturic acid and Benzoic acid were found to be 17.3 and 15.6 minutes, respectively. The detection limit was 0.126 μg/ml, the quantitative estimation unit was 0.38 μg/ml, and the recovery was 97.183%. S-phenyl mercapturic acid showed a linear signal in the domain of 0.5-20 μg/mL. The developed method has been validated through linearity, precision, accuracy, specificity, LOD, and LOQ. Therefore, the proposed analytical method proved its applicability and efficiency in estimating the benzene metabolite in urine.